Capital structure and financial performance: a study on commercial banks in Sri Lanka - Sivalingam, L.; Kengatharan, L. (AESS Publications, 2018)
Purpose of this study was to examine the relationship between capital structure and financial performance of listed licensed commercial banks in Sri Lanka. Panel data were used to conduct the empirical study which were extracted from the annual reports of 10 selected banks for the period from 2007 to 2016. Total debt to total assets ratio, long term debt to total assets ratio, and short term debt to total assets ratio were used to measure the capital structure. Return on assets (ROA), return on equity (ROE) were used as financial performance measures. Size of the banks and growth in banks deposit were considered as control variables. Descriptive statistics, correlations, fixed effect and random effect models were used for the data analysis and then with the results of Hausman Specification Test, fixed effect model was considered as the most suitable model to examine the relationship between capital structure and ROA. According to the model, total debt to total assets ratio was significantly negatively related to ROA, however growth in banks deposit was significantly and positively related to ROA. Size, short term debt to total assets ratio and long term debt to total assets ratio did not show any relationship with ROA. Random effect model was considered as the most suitable model to examine the relationship between capital structure and ROE. As per the model, total debt to total assets ratio was significantly negatively related to ROE, while growth in bank deposit was significantly and positively related to ROE. Short term debt to total assets ratio, long term debt to total assets ratio and size were not significantly related to ROE. Results of the study suggest that financial managers should try to finance from internal sources rather than relying heavily on debt capital in their capital structure. Outcome of the study may useful to the practitioners, investors and decision makers in order to maximize their return from their investments.
Keywords: Total debt to total assets; Long term debt to total assets; Short term debt to total assets; Growth in banks deposit; Bank size; Return on assets; Return on equity.